The Impact of Global Market Environment on the Degree of Cooperation of International Strategic Alliances among Service Firms - Ghasham, Abdullah Ahmed Nasser; Nik Abdullah, Nik Ab Halim; Abd Ghani, Noor Hasmini (International Review of Management and Marketing, 2016)
Globalisation of market present more challenges and it requires firms to respond by adopting various strategies. One of the strategies is through involvement in international strategic alliances. The objective of this study was to investigate the impact of global market environment factors, which consists of two dimensions namely global market opportunities and global market threats on the degree of cooperation of international strategic alliances. A quantitative study with data collected through survey questionnaire was conducted and the sample of the study consisted of 214 service based companies in Yemen. The findings show a significant positive relationship between the global market opportunities factor and the degree of cooperation of international strategic alliances. In contrast, there is no significant relationship observed between the global market threats and the degree of cooperation. Therefore, firms observing new market opportunities resulting from globalization tend to increase the degree of cooperation of their strategic alliances. Keywords: International Strategic Alliances, Global Market Environment, Global Market Opportunities, Global Market Threat, Service Firms, Yemen JEL Classification: M3